2014
DOI: 10.1155/2014/205617
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the H, F, or M Proteins Can Facilitate Resistance of Measles Virus to Neutralizing Human Anti-MV Sera

Abstract: Although there is currently no evidence of emerging strains of measles virus (MV) that can resist neutralization by the anti-MV antibodies present in vaccinees, certain mutations in circulating wt MV strains appear to reduce the efficacy of these antibodies. Moreover, it has been hypothesized that resistance to neutralization by such antibodies could allow MV to persist. In this study, we use a novel in vitro system to determine the molecular basis of MV's resistance to neutralization. We find that both wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…The HIV-infected patients with MV CNS manifestations identified in the South African epidemic, from whom the variant viruses were isolated, all had low CD4 + T-cell lymphocyte counts, suggesting that those who developed fatal encephalitis had impaired cellular immunity and failed to clear the viral infection in the usual time frame ( 1 , 11 , 12 ). As another explanation for why immune clearance may have failed, it is noteworthy that alterations in MV H, F, or M proteins have been shown to permit MV to escape neutralizing human anti-MV sera in vitro ( 58 ), and some of these mutations were located within several residues of L454W (e.g., L457W). It is feasible that even in the presence of humoral immunity, F L454W may have arisen as an antibody escape variant and replicated without cellular immunity surveillance, despite not being a predominant species in the blood of one of the patients during acute measles; however, the fact that the L454W F-bearing recombinant virus is neutralized by human serum makes this less likely.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-infected patients with MV CNS manifestations identified in the South African epidemic, from whom the variant viruses were isolated, all had low CD4 + T-cell lymphocyte counts, suggesting that those who developed fatal encephalitis had impaired cellular immunity and failed to clear the viral infection in the usual time frame ( 1 , 11 , 12 ). As another explanation for why immune clearance may have failed, it is noteworthy that alterations in MV H, F, or M proteins have been shown to permit MV to escape neutralizing human anti-MV sera in vitro ( 58 ), and some of these mutations were located within several residues of L454W (e.g., L457W). It is feasible that even in the presence of humoral immunity, F L454W may have arisen as an antibody escape variant and replicated without cellular immunity surveillance, despite not being a predominant species in the blood of one of the patients during acute measles; however, the fact that the L454W F-bearing recombinant virus is neutralized by human serum makes this less likely.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the PEA motif has its effect by a similar mechanism. Previously we showed that mutations in the M protein can affect the conformation of the F and H glycoproteins and thus facilitate resistance to neutralizing anti-MV sera [ 19 ]. Presumably, the PEA motif in the M proteins of wt MV strains induces a particular 3D conformation in the glycoproteins that allows an elevated immune escape and hence an increased potential for persistence.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we showed that vaccine/laboratory strains of MeV are susceptible, like wt MeV strains, to accumulate mutations in their H, F, and M proteins under immune pressure [ 19 ]. However, it would appear that, unlike wt MeV, they lack a phenotypic marker that allows spread and persistence in the CNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in the M protein results in the failure to form virus particle facilitating persistence of measles virus in neuronal cells. Failure to form virus particle also helps virus evading neutralizing antibodies …”
Section: Genetic Differences Between Sspe Viruses and Wild Measles Virusmentioning
confidence: 99%